Bersaing Terhadap Kinerja Pemasaran (Studi Kasus pada Pengusaha Tambak Ikan di Desa Gondosuli Kecamatan Gondang Kabupaten Tulungagung) - Nicholas Galang Widjanarko; Rois Arifin; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted in Gondosuli Village, Gondang District, Tulungagung Regency. This type of research uses a quantitative approach with descriptive data analysis. The purpose of this study was to determine and analyze the effect of entrepreneurial orientation, customer orientation and competitive advantage on marketing performance. The independent variables used are entrepreneurial orientation, customer orientation and competitive advantage. while the dependent variable is marketing performance. The sample used in this study were 50 fishpond entrepreneurs in Gondosuli Village, Tulungagung. Data collection techniques using a questionnaire. The analytical method used is instrument test, multiple linear regression analysis, classical assumption test, determination test, F test and T test using SPSS 16.0 computer software for data processing. The results of this study indicate that entrepreneurial orientation affects marketing performance, customer orientation affects marketing performance and competitive advantage affects marketing performance. entrepreneurial orientation, customer orientation and competitive advantage simultaneously affect marketing performance. Keywords: Entrepreneurial Orientation, Competitive Advantage Customer Orientation And Marketing Performance